PENGENDALIAN KUALITAS PRODUK NPK PHONSKA DENGAN METODE STATISTICAL PROCESSING CONTROL PADA UNIT PRODUKSI 2A PT. PETROKIMIA GRESIK. - Abdurrahman Faris Indriya Himawan; Muhammad Abidhin Al Habtsi (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2019)
This study aims to determine the quality control of Phonska NPK fertilizer using Statistical Processing Control method. Statistical Processing Control to analyze and identify quality deviations in Phonska NPK products. There were five people in this study. Data collection techniques using observation, interviews and documentation. Data analysis techniques using Statistical Processing Control. PT. Petrokimia Gresik has Phonska NPK fertilizer products whose production has deviations but can be overcome using the SPC method (Statistical Processing Control).